A Systematic Literature Review of Contingency Theory in Management Accounting and Control Systems (2010–2024) - Norman Silalahi; Sambas Ade Kesuma (Universitas Persada Indonesia YAI, 2025)
Contingency theory is one of the conceptual frameworks that is widely used in managementaccounting research and management control systems. This theory assumes that theeffectiveness of accounting and control systems cannot be universally determined, but ratheris influenced by the compatibility between organizational characteristics and the contextualfactors that surround them. Although this theory has been a major reference in variousempirical studies, there has not been a systematic review that comprehensively maps howcontingency theory is applied, developed, and integrated with other theories in the context ofmodern management accounting.This study aims to conduct a systematic literature review (SLR) of studies that applycontingency theory in the field of management accounting and management control systemsduring the period 2010 to 2024. This study uses an approach that refers to the guidelines ofKitchenham and Charters (2007), with the stages of planning, implementation, and reportingwhich include automatic and manual literature search, application of inclusion-exclusioncriteria, quality assessment, and data extraction process.The results of the review show that most studies combine contingency theory with othertheories such as Institutional Theory, Resource-Based View, and Agency Theory to strengthenthe conceptual foundation. The most frequently studied contextual variables includeenvironmental uncertainty, organizational strategy, company size, and technology support. Inaddition, the quantitative approach with Structural Equation Modeling (SEM) or Partial LeastSquares (PLS) survey and analysis methods dominated the studies studied.Theoretically, this study contributes by presenting a comprehensive picture of the developmentand direction of research based on contingency theory. The results of this study are expectedto be the basis for the development of a conceptual model that is more adaptive toorganizational dynamics and an increasingly complex business environment.Keywords: contingency theory, management accounting system, management control system,systematic literature review, management accounting.